Cooling of a processor with the use of a heat pump = Chłodzenie procesora za pomocą pompy ciepła - Lipnicki, Zygmunt; Lechów, Hanna; Pantoł, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper the problem of cooling a component, in the interior of which heat is generated due to its work, was solved analytically. the problem of cooling of a processor with the use of a heat pump was solved based on a earlier theoretical analysis of authors of external surface cooling of the cooled component by using the phenomenon of liquid evaporation. Cases of stationary and non-stationary cooling were solved as well.
Keywords: heat pumps; cooling; processor; vaprocompressor cycle; evaporation; pompa ciepła; chłodzenie; procesor; cykl sprężania pary; odparowywanie